A qualitative study on healthcare professionals' perceived barriers to insulin initiation in a multi-ethnic population - Lee, Y.K.; Lee, P.Y.; Ng, Chirk Jenn (BioMed Central, 2012)
Background: Nationwide surveys have shown that the prevalence of diabetes rates in Malaysia have almost doubled in the past ten years; yet diabetes control remains poor and insulin therapy is underutilized. This study aimed to explore healthcare professionals' views on barriers to starting insulin therapy in people with type 2 diabetes. Methods: Healthcare professionals consisting of general practitioners (n = 11), family medicine specialists (n = 10), medical officers (n = 8), government policy makers (n = 4), diabetes educators (n = 3) and endocrinologists (n = 2) were interviewed. A semi-structured topic guide was used to guide the interviews by trained facilitators. The interviews were transcribed verbatim and analysed using a thematic analysis approach. Results: Insulin initiation was found to be affected by patient, healthcare professional and system factors. Patients' barriers include culture-specific barriers such as the religious purity of insulin, preferred use of complementary medication and perceived lethality of insulin therapy. Healthcare professionals' barriers include negative attitudes towards insulin therapy and the 'legacy effect' of old insulin guidelines; whilst system barriers highlight the lack of resources, language and communication challenges. Conclusions: Tackling the issue of insulin initiation should not only happen during clinical consultations. It requires health education to emphasise the progressive nature of diabetes and the eventuality of insulin therapy at early stage of the illness. Healthcare professionals should be trained how to initiate insulin and communicate effectively with patients from various cultural and religious backgrounds.